Wilderness, gender, and identity in selected writings by contemporary American Women - Moghadam, Davood Mohammadi (2015)
Wilderness has so generally been reckoned a male domain and not the place of women;the moments a woman steps into this masculine sphere her femininity is in question. Hence nature writing studies underestimated women‘s wilderness writing. Furthermore,studies on human identity paid scant attention to the role of natural environment in defining human identity. To challenge the above insufficiencies in literature, this study investigates the effect of wilderness on the feminine identity of women in three contemporary American women‘s wilderness writing- Woodswoman by Anne LaBastille, Becoming Odyssa by Jennifer Pharr Davis and Wild by Cheryl Strayed. All these three women dare to venture into wilderness without the companion of any man,and have written about their first hand wilderness experiences. This study focuses on the outcomes and characteristics of wilderness as a transformative area for women to know better their physical and spiritual ―self.‖ Ecocriticism offers the requisite foundation for the current study since this approach speaks about human/nature relationship and apt for reading non-fiction nature writings. Because this ecocritical study concentrates on the redefinition of identity through a close experience of pure natural environment in wilderness, Susan Clayton‘s theory of environmental identity is mainly utilized in this research. Other concepts like ‗wilderness rites of passage‘ and ‗forms of identity construction‘ are borrowed from other scholars like Foster & Little and Castells to strengthen the conceptual framework. The studies on the effects of wilderness on human, done in the field of psychology, also play an important role in our conceptual framework. The study concludes that being faraway from society and its socio-cultural norms, wilderness offers a context entirely different from social one for the women in the current study. Although in different ways, all these women feel themselves competent and autonomous at the end of their wilderness journey. The main gift that a wilderness journey bestows on these women is their empowered sense of connection and their change in perspective on the notion of feminine body and feminine appearance/beauty albeit in different ways. Accordingly, they are able to challenge the traditional femininity prescribed for them and to reach a sense of selfactualization,hence to reconstruct a new feminine identity.